Three-dimensional interferometric stage encoder using a single access port - Wiseman, Kieran B.; Kissinger, Thomas; Tatam, Ralph P. (Cranfield University, 2020)
Research Data for Paper "Three-dimensional interferometric stage encoder using a single access port" by Kieran B. Wiseman, Thomas Kissinger and Ralph P. Tatam, Cranfield University, UK
Keywords: interferometric technique'; 'interferometric measurements'; 'Optical Encoding'; 'metrology applications'; 'metrology technique'; 'Photonics; Optoelectronics and Optical Communications'; 'Nanometrology'